Villonodular synovitis in the dog - Åkerblom, S.; Sjöström, L. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
Four cases of villonodular synovitis were diagnosed by histopathology. All four dogs were treated medically with either carprophen or a combination of carprophen and glucosamine complex (Cosequin®). In three of the dogs the condition improved significantly, and these dogs returned to normal workload.
Keywords: Villonodular synovitis; arthroscopy; medical treatment; shoulder joint; stifle joint; dog